Peran Guru Bimbingan Dan Konseling Dalam Pembinaan Karakter Siswa Sekolah Menengah Pertama Majelis Tafsir Al-Quran (Smp Mta) Gemolong Islamic Boarding School Tahun Pelajaran 2015/2016 - Fitriah, Fitriah; , Drs. Abdullah Mahmud, M. Ag (2016)
Establishing and nurturing the character of students is not an easy thing for a teacher. In Majelis Tafsir Al-Quran Junior High School (SMP MTA) at Gemolong student's character building is the main responsibility of guidance and counseling teacher, though in essence the student's character building is the responsibility of all parties in the school. To change the character of the students become better, aligned with the norms, customs and religious Shari'ah. In shaping the noble character and good behavior then the teacher's of SMP MTA head to take several attempts in student's character building of students. The objectives of this study is to describe factors, role of BK teacher's of SMP MTA, school year 2015/2016 in building the student's character. This research is a field research, the approach used is a qualitative approach. Collecting data using interviews, observation and documentation. Methodology of research is descriptive - qualitative method. Based on data analysis, it can be concluded that the role BK theacher's of SMP MTA role in the process student character building is using techniques of counseling, advice, group guidance, group counseling, learning with guidance techniques acquired with the role's of: a) provide motivation, escort and supervision to students, b) admonish and advise students who violate school and or dormitory rules, c) analyze the level of intelligence, talents, and interests of students, d) help to solve students' problems and provide solutions on issues perceived each group, e) provide an understanding, deepening, and coaching related everyday life, the strengthening of moral and doctrinal. Character building in schools supported also coaching in the boarding and at home. Couching at the boarding include by studies after daily prayers, charging daily prayer, hadith, paragraph options, chronicle, free prayer, muhadatsah conversation, tahfidz, tahsin, speech, mentoring room, dan night study. And also good habituation and discipline applied in boarding. Character building at home with apply good parenting and parents become qudwah hasanah at home. Difficulties of BK teachers in coaching characters are parents who can not be asked to be wise in consultation problems related to their child, troubled students are difficult to explain their problem honestly, the lack of cooperation between BK teachers and subject teachers, culture and wrong parenting in educating their son in the house, Strain or coercion of parents in sending children to school, and student socially wrong and becomes a habit inherent.